Density‐dependent effects of a widespread invasive herbivore on tree survival and biomass during reforestation. Issue 4 (29th April 2015) - Forsyth, David M.; Scroggie, Michael P.; Arthur, Anthony D.; Lindeman, Michael; Ramsey, David S. L.; McPhee, Steven R.; Bloomfield, Tim; Stuart, Ivor G.
Abstract : Reforestation has been widely adopted as a solution to multiple global change issues. However, the role of herbivory by invasive species in the restoration of grassland to forest has received little attention. We conducted a field experiment to investigate the impacts of a widespread invasive mammalian herbivore, the European rabbit ( Oryctolagus cuniculus ), on trees planted in a landscape‐scale reforestation program in south‐eastern Australia. Three native tree species were planted inside and outside rabbit‐proof exclosures within 10 experimental units, and a random half of the units were subjected to intensive and sustained rabbit control for the remainder of the experiment. Quarterly survival of trees, and total aboveground biomass at the conclusion of the experiment, were estimated using hierarchical Bayesian models. Control substantially reduced rabbit densities on the five treatment units relative to the five non‐treatment units. Survival of trees planted outside exclosures was highest at lowest rabbit density and declined non‐linearly with increasing rabbit density for all three tree species, but even very low rabbit densities had strong negative effects on the survival of trees outside exclosures. There was a three‐way interaction between tree height, being outside an exclosure, and rabbit density. Smaller trees planted outside exclosures always had substantially lower overall survival than trees of the same height planted inside exclosures, and the magnitude of the difference increased with increasing rabbit density. Increasing rabbit densities reduced the overall survival of increasingly taller trees of all three species planted outside exclosures. The aboveground biomass of trees surviving outside exclosures was significantly greater in treatment units compared with non‐treatment units for all three species. The combined effects of differential survival and accumulation of aboveground biomass led to higher biomasses inside exclosures relative to outside exclosures just 21 months after planting. The aboveground biomass of trees planted outside exclosures declined with increasing rabbit density, and was effectively zero when rabbit densities exceeded 100 active warren entrances/ha. These results demonstrate that invasive herbivores can rapidly arrest the conversion of grassland to forest. Invasive herbivores such as the European rabbit may need to be completely excluded in order to maximize the benefits of reforestation.